KEANEKARAGAMAN JENIS KANTONG SEMAR (Nepenthes spp.) PADA KONDISI TEMPAT TUMBUH HUTAN RAWA GAMBUT DAN HUTAN KERANGAS DI DALAM DAN SEKITAR KHDTK UNTAN - Virgiawan Welandika; Ratna Herawatiningsih; Wiwik Ekyastuti (Universitas Tanjungpura, 2019)
Nepenthes is an unique ornamental plant that have various benefits and high aesthetic value. This species is a protected species. West Kalimantan is one of the nepenthes distribution habitats. This research was conducted in the Forest Areas with Special Purpose (KHDTK) Universitas Tanjungpura (UNTAN), Landak Regency. The purpose of this study is to obtain the data of Nepenthes species diversity on the conditions in which peat swamp forests and kerangas forests grow in and around the KHDTK UNTAN. The method used are survey method with a sampling technique using a double plot with a size of 2m x 2m. The results showed that there were 3 types of Nepenthes found; N. ampullaria Jack, N. mirabilis Druce and N. rafflesiana Jack. Nepenthes species diversity in both habitats is low, in peat swamp forest the value of Nepenthes species diversity is 0,198 and in kerangas forest value is 0,035.Keywords: Nepenthes, Species Diversity, Habitat, Peat Swamp, Kerangas